2014
DOI: 10.1111/chd.12179
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Imbalances in Patients with Congenital Cardiac Defects: A Meta-analysis Reveals Novel Potential Critical Regions Involved in Heart Development

Abstract: The pattern of chromosomal imbalances in patients with congenital cardiac defects suggests that many loci may be involved in normal heart development, some with very strong and direct effects and others with less direct effects. Chromosomal duplication/deletion mapping will provide an important roadmap for genome-wide sequencing and genetic mapping strategies to identify novel genes critical for heart development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Heart disease patients with distal deletion 22q11.2 have a broad spectrum of cardiac defects such as septal defects, tetralogy of Fallot, and conotruncal defects [Breckpot et al, 2012]. The deletion involving only the TOP3B gene was reported in 2 patients in the study by Thorsson et al [2015], and both presented CHD. However, the role of TOP3B in cardiac development still needs to be further studied because, even though TOP3B is also expressed in the heart, deletions or mutations of this gene are more frequently described in patients with neurological developmental delay [O'Roak et al, 2012;Stoll et al, 2013].…”
Section: Discussionmentioning
confidence: 96%
“…Heart disease patients with distal deletion 22q11.2 have a broad spectrum of cardiac defects such as septal defects, tetralogy of Fallot, and conotruncal defects [Breckpot et al, 2012]. The deletion involving only the TOP3B gene was reported in 2 patients in the study by Thorsson et al [2015], and both presented CHD. However, the role of TOP3B in cardiac development still needs to be further studied because, even though TOP3B is also expressed in the heart, deletions or mutations of this gene are more frequently described in patients with neurological developmental delay [O'Roak et al, 2012;Stoll et al, 2013].…”
Section: Discussionmentioning
confidence: 96%
“…One attempt at a meta-analysis identified dozens of putatively associated loci. 52 Other CNVs appear so rarely that recurrence has not yet been observed. Most studies have reported only CNVs involving autosomes; sex chromosome copy number findings may also be relevant to CHD.…”
Section: Genome-wide Cnv In Chdmentioning
confidence: 99%
“…38,39,45,47,50,55,57,67,68 As for all CNVs associated with CHD, the expression is variable, even within families, for both cardiac anomalies and other phenotypes, and is not necessarily correlated with the length of the CNV. 38,40,47,52,67,69 1q21.1 duplications are rare in control populations, e.g., in five out of 18,828 controls (0.027%) from three studies, where some controls were not screened for disease (reviewed in ref 67). Although it is uncertain if any single gene at this locus can be designated as truly causal, the most evidence points to the GJA5 gene that encodes connexin 40, 38,68 a cardiac gap junction protein expressed in the right ventricular outflow tract.…”
Section: Genome-wide Cnv In Chdmentioning
confidence: 99%
“…Only two other cases of HEY2 duplications with molecular cytogenetic descriptions have been previously reported in the literature [Thorsson et al, 2014]. Although these cases may provide some additional evidence that HEY2 duplications may contribute to the development of clinical phenotypes, their usefulness is limited by the large sizes of the chromosome 6q duplications involved, the presence of large or clinically relevant deletions on other chromosomes in the same individual and a paucity of clinical information.…”
Section: Discussionmentioning
confidence: 99%